The Impact Of Using Social Media Influencer On Brand Awareness To Purchase Intention At Scarlett Whitening (Survey On Gen Z) - Hartanto, Adelina Jessika; Zuliestiana, Dinda (eProceedings of Management, 2023)
The background of this research is that there are problems that occur in the ranking of the Scarlett Whitening companyrelated to product sales. Scarlett Whitening occupies the second position as a top local brand. Therefore, this studywas conducted with the aim of examining the variables to be studied in this study, namely, Social Media Influencers,Brand Awareness and Purchase Intentions on Scarlett Whitening in generation Z. Scarlett uses SMI for branding andselling their products. An influencer usually has a large number of followers on social media and is generally able toinfluence the thoughts and actions of his followers to follow the influencer. This study uses quantitative researchmethods, using SPSS and SEM Analysis as software programs to analyze data and survey methods to collect data bydistributing questionnaires to Generation Z who live in DKI Jakarta involving 250 participants.The results of the SEMPLSanalysis show that social media influencers have a positive influence on brand awareness and purchaseintentionThe suggestion, Scarlett whitening company to be more selective in determining more interesting and creativeinfluencers in general to attract the attention of Generation, can create more unique characteristicsKata Kunci-Social Media Influencer, Brand Awareness, Purchase Intention, Generation Z